Impact of Genetic Counseling in Women with a Family History of Breast Cancer in Italy. Issue 2 (10th September 2015) - Godino, Lea; Razzaboni, Elisabetta; Bianconi, Margherita; Turchetti, Daniela
Abstract: As the impact of breast cancer (BC) risk assessment in asymptomatic women with a family history of BC had never been explored in Italy, we performed a study on a retrospective series of women who had undergone BC risk assessment. To this aim, a semi‐structured telephone interview was administered to 82 women. Most participants considered the information received as clear (96.2 %) and helpful (76.8 %). Thirty‐eight (46.3 %) stated that their perceived risk of BC had changed after the counseling: for 40.2 % it had decreased, for 6.1 % increased; however, women highly overestimating their risk at the baseline (≥4‐fold) failed to show improvements in risk perception accuracy. Sixty‐six women (80.5 %) stated they had followed the recommended surveillance, while 19.5 % had not, mainly due to difficulties in arranging examinations. Most women (89.0 %) had shared the information with their relatives, with 57.3 % reporting other family members had undertaken the recommended surveillance. BC risk assessment was associated with high rates of satisfaction and had a favorable impact on risk perception in a subgroup of women. The impact on surveillance adhesion extended to relatives. Organized programs for identification and surveillance may help identify a larger fraction of at‐risk women and overcome the reported difficulties in arranging surveillance.